Radionuclide 131I-labeled albumin-indocyanine green nanoparticles for synergistic combined radio-photothermal therapy of anaplastic thyroid cancer - Zhang, Xuemei; Yan, Ziyu; Meng, Zhaowei; Li, Ning; Jia, Qiang; Shen, Yiming; Ji, Yanhui (Frontiers in Oncology, 2022)
Objects: Anaplastic thyroid cancer (ATC) cells cannot retain the radionuclide iodine 131 (131I) for treatment due to the inability to uptake iodine. This study investigated the feasibility of combining radionuclides with photothermal agents in the diagnosis and treatment of ATC. Methods: 131I was labeled on human serum albumin (HSA) by standard chloramines T method. 131I-HSA and indocyanine green (ICG) were non-covalently bound by a simple stirring to obtain 131I-HSA-ICG nanoparticles. Characterizations were performed in vitro. The cytotoxicity and imaging ability were investigated by cell/in-vivo experiments. The radio-photothermal therapy efficacy of the nanoparticles was evaluated from the cellular and in vivo levels. Results: The synthesized nanoparticles had suitable size (25-45 nm) and objective biosafety. Under the irradiation of near-infrared light, the photothermal conversion efficiency of the nanoparticles could reach 24.25%. In vivo fluorescence imaging and SPECT/CT imaging in small animals confirmed that I-HSA-ICG/131I-HSA-ICG nanoparticles could stay in tumor tissue for 4-6 days. Compared with other control groups, 131I-HSA-ICG nanoparticles had the most significant ablation effect on tumor cells under the irradiation of 808 nm laser. Conclusions: In summary, 131I-HSA-ICG nanoparticles could successfully perform dual-modality imaging and treatment of ATC, which provides a new direction for the future treatment of iodine-refractory thyroid cancer.